(untitled) (Asian Journal of Agriculture, 2021)
Abstract. Debache K. 2021. Growth performance of novel food based on mixture of boiled-dried granulated Tenebrio molitor larvae and date-fruit waste in broiler chicken farming. Asian J Agric 5: 22-28. The present study was conducted to evaluate the growth performance of a new diet based on mixture of boiled-dried granulated Tenebrio molitor larvae (Tm) and date-fruit waste (Dw) in broiler chicken diet. A total of 56 two-day old broilers were randomly allotted to 4 dietary groups each with 2 replicates consisting of 7 broilers (C1, C2, Diet1 and Diet2). Equal mixture of three commercial cereal-based diets (chick starter feed, chick grower feed, and chick finisher feed) was formulated. The first control (C1) was 100% the commercial mixture. Second control (C2) is obtained by mixing 50% commercial mixture with 50% Dw. While the other groups (Diet1 and Diet2) were formulated by adding three ingredients at different proportions: 50% commercial mixture: 40% Dw: 10% Tm (Diet1) and 50% commercial mixture: 10% Dw: 40% Tm (Diet2). After the evaluation of daily body weight, clinical signs, specific growth rate and other clinical tests, the chickens were slaughtered at 60 days. Hematological, biochemical, copro-parasitological, and bacterial investigations were performed based on samples taken day 60. Weight gain of broilers fed with Diet1 was almost like broilers fed with first control (C1) diet. However, those fed with Diet2 were significantly (P<0.05) higher than all other dietary groups (C1, C2 and Diet1). Hematological and serum biochemical traits showed no dietary adverse effect, and copro-parasitological diagnosis was negative in all different dietary groups. Moreover, similar microbial communities were detected in digestive system parts of the same animal, no matter in relation to Tm inclusion or no. In conclusion, the overall results collected in this current study propose that date-fruit waste could be used as an exclusive feed for T. molitor insect rearing and dietary inclusion of mixture Dw-Tm into broilers meal could become a partial substitute for commercialized cereal-based diet without affecting the health of broilers.